Determinants of villagers’ satisfaction with post-disaster reconstruction: Evidence from surveys ten years after the Wenchuan earthquake - Ao, Yibin; Zhong, Jinglin; Zhang, Zijun; Han, Lili; Wang, Yan; Chen, Yunfeng; Wang, Tong (Frontiers in Environmental Science, 2022)
Residents' satisfaction with post-disaster reconstruction in earthquake-stricken areas directly affects their quality of life and is an important factor that cannot be ignored in post-disaster reconstruction. After more than ten years of the Wenchuan earthquake, we have taken in this research ten randomly selected villages in the five hardest-hit areas of Wenchuan earthquake as research objects, and obtained 483 valid sample data through the field questionnaire survey. Villagers are randomly sampled and descriptive statistical analysis, factor analysis and ordered logistic regression are used to explore the influencing factors and relationships of villagers' satisfaction with post-disaster reconstruction in Wenchuan earthquake-stricken areas. The results show that: (1) The more rural residents know about post-disaster reconstruction, the higher their satisfaction; (2) The more the annual income increase of families after resettlement, the higher the satisfaction of rural residents with the post-disaster reconstruction; (3) Six public factors, namely the village committee acts as, housing construction quality, public service, policy of benefiting farmers, cultural environment and hardware environment, all significantly affect the overall satisfaction of residents in post-earthquake reconstruction positively. This study thus enriches the theory of residents' satisfaction studies and the practice of post-earthquake reconstruction.